If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -7 = 39 Reorder the terms: -7 + 4y = 39 Solving -7 + 4y = 39 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4y = 39 + 7 Combine like terms: -7 + 7 = 0 0 + 4y = 39 + 7 4y = 39 + 7 Combine like terms: 39 + 7 = 46 4y = 46 Divide each side by '4'. y = 11.5 Simplifying y = 11.5
| 0.5n-5=3n-25 | | 2x-5=39(7+2x) | | 2sin(x)-4-cos(x)=0 | | 6u-6=-9(u-1) | | ifBC=RLthen | | 36+12m^2+m^4=0 | | 4a*3a= | | ln(6x+2)=ln(3x-19) | | -4.3-3z-2.9-z=-3z+5.7 | | -8m-8n+p-2=-10n-9p+8 | | 12*x^2-4=0 | | t(2t+-1)=1 | | 10-(4x-1)=8-5x | | 7x+21(2x-3)=180 | | 8c*3c= | | 3x+22x-4=5(5x+6) | | (-7b+4a)+(-6a-9b)= | | 5w^2+39w+5y=0 | | 9a+19=100 | | X^2-2x+528=0 | | 98=-2(-8x+8) | | 8cos^2x-4cosx-2=0 | | 6g=6g+-34 | | 3x+x+7=6x-2x+7 | | 0.25d+6=11 | | =5x | | N-3.5=6.5 | | 9f+15=15 | | (xy^2+y)dx+(x^2y-x)dy=0 | | 3+x/2=10 | | 8=4(b-2)+4 | | 32=-5x-8 |